2022
DOI: 10.7759/cureus.21000
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study of Intensity-Modulated Radiation Therapy Versus Three-Dimensional Conformal Radiation Therapy With Concurrent Chemotherapy in Locally Advanced Carcinoma Cervix

Abstract: Background: External Beam Radiotherapy is the treatment of choice of locally advanced carcinoma cervix (LACC). The two techniques, three-dimensional conformal radiotherapy (3DCRT) and intensity-modulated radiotherapy (IMRT), have been compared previously in terms of outcomes and toxicities. IMRT has still not shown any benefit over 3DCRT in terms of local control and survival. Hence, the present study was conducted to compare local control and toxicities among both techniques.Material & Methods: Fifty-four pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Various studies have shown the effects of IMRT in reducing irradiated Volumes of rectum, bladder bone marrow and small bowels [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Because of use of multiple beams angles and optimized intensity beams.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown the effects of IMRT in reducing irradiated Volumes of rectum, bladder bone marrow and small bowels [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Because of use of multiple beams angles and optimized intensity beams.…”
Section: Discussionmentioning
confidence: 99%
“…In 3D-CRT with four-field box technique, small bowel within the radiation field is homogeneously irradiated with the targets [16].…”
Section: Discussionmentioning
confidence: 99%